Nano-silver particles, preparation method thereof and conductive ink
By mixing solid polyethylene glycol and silver salt and heating reduction reaction, nanosilver particles with uniform particle size were prepared, which solved the problem of difficult control of nanosilver particles size and high production cost in the prior art, and achieved efficient and environmentally friendly nanosilver particles preparation.
Patent Information
- Application Number
- CN202311318368.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has large dispersion of nanosilver particles when preparing nanosilver particles, and it is difficult to control the particle size. The chemical method requires the use of a large number of chemical reagents, which leads to environmental protection processing problems and high production costs.
By mixing solid polyethylene glycol and silver salt evenly, a viscous mixed material with a solid state at room temperature but a viscosity greater than or equal to 1000 cps at high temperature was obtained, and a heating reduction reaction was carried out to prepare nano silver particles with relatively uniform particle size and narrow distribution.
The particle size uniformity and controllability of nano-silver particles are achieved, which reduces dependence on complex reagents, reduces production costs, and improves environmental protection.
Smart Images

Figure CN119794325A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of new material technology, and in particular to a kind of nano silver particles and a preparation method thereof, and conductive ink. Background Art
[0002] Nanosilver particles are widely used in the production of electronic tags (FIRD), solar cell electrodes, membrane switches, flexible printed circuit boards, organic light-emitting diodes (OLED), transparent conductive films and other products because of their excellent conductivity, oxidation resistance, low-temperature sintering, stable chemical properties, and easy processing. For example, nanosilver particles can show conductive properties close to the original after sintering at a relatively low temperature, so the ink made from them has great application value in the fields of HJT, chip packaging, low-temperature components, etc.
[0003] The preparation methods of nanosilver particles mainly include physical methods such as gas phase condensation, atomization, etc. and chemical methods such as thermal decomposition, liquid phase reduction, etc. However, the size of nanosilver particles prepared by physical methods is widely dispersed and easy to form hard agglomerates; chemical methods mostly use liquid phase reduction, which requires the introduction of more chemical reagents at low reaction concentrations, resulting in difficulty in removing organic matter in the system and bringing about environmental treatment problems with a large load. In addition, silver particles are easy to diffuse in the liquid system and agglomerate, making it difficult to control the size of nanosilver particles. Summary of the invention
[0004] In view of this, some embodiments of the present application provide a nanosilver particle and a preparation method thereof, and a conductive ink, wherein the preparation method can prepare nanosilver particles with relatively uniform particle size and narrow distribution, and the materials used for the reaction are simple, without the need for complex reagents, which is more environmentally friendly and cost-saving.
[0005] In a first aspect, some embodiments of the present application provide a method for preparing nanosilver particles, comprising:
[0006] The solid polyethylene glycol and the silver salt are uniformly mixed to obtain a mixed material; the mixed material is solid at room temperature but is viscous with a viscosity greater than or equal to 1000 cps at high temperature; the mixed material is heated to 120°C-200°C and maintained for 2h-12h to perform a reduction reaction, and the nano-silver particles are separated after the reaction is completed.
[0007] In some embodiments, the molecular weight of polyethylene glycol ranges from 600-20,000.
[0008] In some embodiments, the mass ratio between polyethylene glycol and silver salt is 10:1-1:1.
[0009] In some embodiments, the mass ratio between polyethylene glycol and silver salt is 5:1-1:1.
[0010] In some embodiments, the method further comprises: adding an oily dispersant to the mixed material, wherein the ratio of the mass of the oily dispersant to the mass of silver in the silver salt is 0.1%-10%.
[0011] In some embodiments, the ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.5% to 5%.
[0012] In some embodiments, before performing the reduction reaction, the method further comprises:
[0013] Add a low boiling point solvent to the mixed material and heat it to 60°C-80°C to dissolve the mixed polyethylene glycol and silver salt;
[0014] The ratio of the mass of the low boiling point solvent to the total mass of the polyethylene glycol and the silver salt is 4:1-1:1.
[0015] In some embodiments, the low boiling point solvent includes deionized water and ethanol.
[0016] In some embodiments, before performing the reduction reaction, the method further comprises:
[0017] The mixture is heated to a first temperature and maintained for a preset time to remove the low boiling point solvent, wherein the first temperature is less than 120° C. and greater than 80° C.
[0018] In some embodiments, before performing the reduction reaction, the method further comprises:
[0019] After heating to the first temperature and maintaining it for a preset time, an oily dispersant is added, wherein the ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.1%-10%.
[0020] In some embodiments, the ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.5% to 5%.
[0021] In some embodiments, the method further comprises:
[0022] Add thickener to the mixture to increase viscosity;
[0023] The weight of the thickener is 1%-10% of the weight of the mixed material.
[0024] In some embodiments, the thickener comprises high molecular weight polyvinyl alcohol, high molecular weight modified cellulose, or high molecular weight starch.
[0025] In some embodiments, the reduction reaction is carried out in an internal mixer or a stirrer, and air or oxygen is introduced into the internal mixer or a stirrer during the reduction reaction.
[0026] In some embodiments, the flow rate of air or oxygen is 0.01-10 L / min.
[0027] In some embodiments, the aforementioned separation of the silver nanoparticles comprises:
[0028] The material after the reaction is completed is dissolved in water, filtered, washed and dried to obtain nano silver particles.
[0029] In a second aspect, some embodiments of the present application provide a nano-silver particle prepared by the method for preparing nano-silver particles in the first aspect.
[0030] In a third aspect, some embodiments of the present application provide a conductive ink comprising the nanosilver particles of the second aspect.
[0031] Beneficial effects of the embodiments of the present application: Different from the prior art, the method for preparing nanosilver particles provided in the embodiments of the present application is to mix solid polyethylene glycol and silver salt evenly to obtain a mixed material. The mixed material is solid at room temperature but viscous with a viscosity greater than or equal to 1000cps at high temperature. The mixed material is heated to 120°C-200°C and maintained for 2h-12h to perform a reduction reaction, and the nanosilver particles are separated after the reaction is completed. In this embodiment, the mixed material used for the reaction is solid at room temperature and viscous at high temperature. This viscous system at high temperature can effectively limit the diffusion and agglomeration of silver particles, so that the particle size of the nanosilver particles is relatively uniform and narrowly distributed, and its size distribution can be better controlled. In addition, polyethylene glycol is used as both a reducing agent and a reaction medium, the material is simple, no complex reagents are required, and costs can be effectively saved. It can also reduce the use of organic matter and organic solvents, which is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplified descriptions do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and unless otherwise stated, the figures in the drawings do not constitute proportional limitations.
[0033] Figure 1 A schematic diagram of a process for preparing silver nanoparticles in some embodiments of the present application;
[0034] Figure 2 The following are SEM micrographs of the nanosilver particles prepared in some examples of the present application. DETAILED DESCRIPTION
[0035] The present application is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present application, but do not limit the present application in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present application. These all belong to the protection scope of the present application.
[0036] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0037] It should be noted that, if there is no conflict, the various features in the embodiments of the present application can be combined with each other, all within the scope of protection of the present application. In addition, although the functional module division is performed in the device schematic diagram and the logical order is shown in the flow chart, in some cases, the steps shown or described can be performed in a sequence different from the module division in the device or the flow chart. In addition, the words "first", "second", "third", etc. used herein do not limit the data and execution order, but only distinguish the same items or similar items with basically the same functions and effects.
[0038] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this specification and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items.
[0039] In addition, the technical features involved in each embodiment of the present application described below can be combined with each other as long as they do not conflict with each other.
[0040] Nanosilver particles are metallic silver particles with nanometer size, which have low-temperature sintering characteristics, for example, they can be sintered at a temperature of less than 150°C. After sintering, the nanosilver particles show conductive properties close to those of the bulk. Therefore, nanosilver particles are widely used in some conductive products or conductive materials.
[0041] In some scenarios, conductive ink made by using nanosilver particles as conductive fillers has great application value in HJT, chip packaging, low-temperature components and other fields. Conductive ink is a viscous slurry composed of high-purity nanosilver particles, adhesives, solvents, and additives. When the conductive ink is cured and dried, the distance between the nanosilver particles becomes smaller due to the volatilization of the solvent and the volume shrinkage of the adhesive after curing, so that they contact each other, thus forming a conductive path.
[0042] The particle size, distribution and purity of nanosilver particles directly affect the conductive properties of conductive ink. Therefore, it is very important to prepare nanosilver particles with uniform particle size, narrow distribution and controllable size.
[0043] Some methods for preparing nano silver particles known to the inventors of the present application include physical methods (such as gas phase condensation, atomization, etc.) and chemical methods (such as thermal decomposition, liquid phase reduction, etc.). However, the nano silver particles obtained by the physical method have a large size dispersion, usually reaching 1-500nm, are easy to form hard agglomerates, and have little organic matter on the surface. Therefore, it is not conducive to the subsequent preparation of high-performance conductive ink.
[0044] In the chemical method, the liquid phase reduction method is used to prepare nanosilver particles with a size of 1-300nm by adjusting the reaction concentration, temperature, type of reducing agent, feeding and stirring process. However, most solution chemical preparation methods require the introduction of more chemical reagents at low reaction concentrations, which makes it difficult to remove organic matter in the system and brings about a large load of environmental treatment problems. As a result, the production cost of nanosilver particles is high. In addition, silver particles are easy to diffuse in the liquid system and agglomerate, making it difficult to control the size of nanosilver particles.
[0045] In view of this, some embodiments of the present application provide a method for preparing nanosilver particles, wherein solid polyethylene glycol and silver salt are evenly mixed to obtain a mixed material. The mixed material is solid at room temperature but is viscous with a viscosity greater than or equal to 1000cps at high temperature. The mixed material is heated to 120°C-200°C and maintained for 2h-12h to perform a reduction reaction, and the nanosilver particles are separated after the reaction is completed. In this embodiment, the mixed material used for the reaction is solid at room temperature and is viscous with a viscosity greater than or equal to 1000cps at high temperature. This viscous system at high temperature can effectively limit the diffusion and agglomeration of silver particles, so that the particle size of the nanosilver particles is relatively uniform and narrowly distributed, and its size distribution can be better controlled. In addition, polyethylene glycol is used as both a reducing agent and a reaction medium, the material is simple, no complex reagents are required, and the cost can be effectively saved. It can also reduce the use of a large amount of organic matter and organic solvents, which is more environmentally friendly.
[0046] The following describes the method for preparing nano silver particles provided by some embodiments of the present application. Figure 1 As shown, the method S100 includes:
[0047] S10: Evenly mix the polyethylene glycol and the silver salt to obtain a mixed material, wherein the mixed material is solid at room temperature but is viscous with a viscosity greater than or equal to 1000 cps at high temperature.
[0048] S20: heating the mixture to 120° C.-200° C. and maintaining the temperature for 2 h-12 h to perform a reduction reaction, and separating the nano-silver particles after the reaction is completed.
[0049] Among them, silver salt is a salt whose cation is silver ion, for example, it can include silver nitrate or silver acetate or other organic carboxylic acid silver. Silver nitrate is a white crystalline powder at room temperature, and silver acetate is a grayish white solid powder at room temperature. It is understandable that silver salt provides silver raw material for preparing nano silver particles. Those skilled in the art can select a suitable silver salt according to actual conditions for reducing metallic silver.
[0050] Among them, polyethylene glycol is gradually polymerized from ethylene oxide, or gradually polymerized from ethylene glycol. Polyethylene glycol exhibits different properties depending on its molecular weight. When the molecular weight is 200-600, polyethylene glycol is liquid; when the molecular weight is above 600, it gradually becomes a semi-solid, waxy solid.
[0051] After a certain amount of polyethylene glycol and silver salt are mixed evenly, the obtained mixture is solid or viscous at room temperature. In some embodiments, polyethylene glycol with a molecular weight greater than 600 can be used to mix with silver salt, and the mixture is solid at room temperature but viscous with a viscosity greater than or equal to 1000cps at high temperature. In some embodiments, polyethylene glycol with a molecular weight range of 600-20000 can be used to mix with silver salt. In some embodiments, polyethylene glycol with a molecular weight range of 1000-10000 can be used to mix with silver salt. It is understandable that polyethylene glycol with a molecular weight range of 1000-10000 is in a waxy solid state, and the silver salt is also in a solid state, so that the mixture composed of the two is in a solid state.
[0052] It is understood that the purpose of mixing polyethylene glycol and silver salt uniformly is to allow polyethylene glycol and silver salt to fully contact, fully react under the subsequent reaction conditions, improve reaction efficiency, and improve the efficiency of preparing nano silver particles. In some embodiments, polyethylene glycol and silver salt can be put into a certain weight ratio in an internal mixer, a stirrer or a kneader for stirring and mixing uniformly to prepare for subsequent reactions. In some embodiments, polyethylene glycol and silver salt can also be put into other equipment in a certain weight ratio for stirring and mixing uniformly, and then the mixture is transferred to an internal mixer, a stirrer or a kneader to prepare for subsequent reactions. It is understood that, unlike the liquid phase method for reducing nano silver, which needs to be carried out in a reactor, the mixture in this solution is solid at room temperature and viscous at high temperature with a viscosity greater than or equal to 1000cps, so that the entire reduction reaction process can be carried out in an internal mixer, a stirrer or a kneader.
[0053] Then, the mixture is heated to 120°C-200°C and maintained for 2h-12h to provide reaction conditions for the reduction reaction. Taking the silver salt as silver nitrate as an example, at this temperature, polyethylene glycol and silver nitrate gradually react, and polyethylene glycol is used as a reducing agent to reduce the silver ions in the silver salt to metallic silver. Both gradually melt during the high-temperature reaction, and the entire material system is in a viscous state. Compared with the liquid system, the viscous state can effectively limit the diffusion and agglomeration of silver ions, so that the particle size of the nanosilver particles is more uniform and narrowly distributed, and its size distribution can be better controlled. For example, the particle size of the prepared nanosilver particles is uniformly distributed in 50-100nm. In some embodiments, the silver particles in the nanosilver particles are spherical, and their particle size distribution is 50-100nm.
[0054] It is understandable that polyethylene glycol is used as both a reducing agent and a reaction medium, so that the entire reduction reaction does not require complex reagents, which can effectively save costs. On the contrary, the known liquid phase reduction method uses a variety of organic or inorganic compounds as reducing agents, ethylene glycol or polyethylene glycol as solvents, and polyvinyl pyrrolidone (PVP) as a protective agent, which not only introduces a large amount of organic matter and organic solvents, but also makes it difficult to remove organic matter in the system and brings about a large load of environmental protection treatment problems; and the silver salt concentration is low, and its mass proportion is generally less than 10%, because when the silver salt concentration is high, nanosilver is prone to aggregation and enlargement in a liquid system, resulting in difficult to control size. In other words, the liquid phase reduction method has the problems of difficult to control the size of nanosilver, low production efficiency, and environmental protection.
[0055] Compared with the liquid phase reduction method, polyethylene glycol is used as a reducing agent and a reaction medium, and the materials are simple, no complex reagents are required, and the cost can be effectively saved. The use of a large amount of organic matter and organic solvents can also be reduced, which is more environmentally friendly. In addition, polyethylene glycol is different from the dangers of hydrazine hydrate, sodium borohydride, etc., and it is relatively mild and easy to use. Polyethylene glycol can be easily removed from the surface of nano silver particles, so that the subsequent surface treatment of nano silver particles can be conveniently performed to obtain nano silver particles with higher purity.
[0056] In addition, the system in the present application that is in a viscous state at high temperature can effectively limit the diffusion and agglomeration of silver particles, so that the particle size of the nano-silver particles is relatively uniform and narrowly distributed, and its size distribution can be better controlled. It can be understood that the higher the mass proportion of silver nitrate, the more nano-silver particles are prepared, and the easier it is to aggregate and grow and agglomerate. Therefore, the system that is in a viscous state at high temperature is conducive to the reduction preparation with a high mass proportion of silver salt. In the reaction materials, the mass proportion of silver salt is high, which can provide more silver raw materials, thereby improving the production efficiency of nano-silver particles.
[0057] In some embodiments, the mass ratio between polyethylene glycol and the silver salt is 10:1-1:1. In this embodiment, different from the liquid phase reduction method in which the proportion of silver salt is usually less than 10%, in this embodiment, the mass proportion of silver salt is relatively high, which can be higher than 10%, thereby achieving a high concentration reduction reaction. Optionally, the mass ratio between polyethylene glycol and the silver salt is 5:1-1:1. In this embodiment, the mass proportion of silver salt is higher than 16% and lower than 50%, which can provide more silver raw materials, thereby improving the production efficiency of nanosilver particles.
[0058] The solid or viscous system can effectively limit the diffusion and agglomeration of silver particles. Even when the mass proportion of silver salt is high, that is, when the concentration of the generated nanosilver particles is high, its size distribution can be better controlled, so that the particle size of the nanosilver particles is relatively uniform and the distribution is narrow, and the production efficiency can be improved.
[0059] In some embodiments, the method S100 further includes:
[0060] S30: adding an oily dispersant to the mixed material, wherein the ratio of the mass of the oily dispersant to the mass of silver in the silver salt is 0.1%-10%.
[0061] Among them, the oily dispersant can be oleic acid or stearic acid, etc. In some embodiments, the oily dispersant can be added when the polyethylene glycol and the silver salt are mixed, so that the oily dispersant, the polyethylene glycol and the silver salt are fully mixed. For example, polyethylene glycol, silver nitrate and oleic acid can be put into a mixer, a stirrer or a kneader at a certain weight ratio (for example, 2:1:0.006) to stir and mix evenly to prepare for subsequent reactions.
[0062] The oily dispersant is used to protect the nanosilver particles generated by the reaction. Specifically, the carboxyl groups in the oily dispersant interact with the surface of the nanosilver particles, wrapping the nanosilver particles, which can effectively prevent the nanosilver particles from agglomerating and growing, thereby facilitating the control of the size distribution of the nanosilver particles, making the particle size of the nanosilver particles more uniform and narrowly distributed.
[0063] It is understandable that the oily dispersant can help control the size of the nano-silver particles and improve the uniformity of the size. In order to prevent the oily dispersant from remaining in the nano-silver particles and affecting the conductivity of the nano-silver particles when used as a conductive product, in this embodiment, the mass of the oily dispersant is set to 0.1%-10% of the mass of the silver in the silver salt based on the mass of the silver in the silver salt. Optionally, the mass of the oily dispersant is set to 0.5%-5% of the mass of the silver in the silver salt. Thus, providing a reasonable amount of oily dispersant can protect the nano-silver particles, help control the size, and improve the uniformity of the size, without affecting its conductivity due to excessive oily dispersant.
[0064] In some embodiments, before performing the reduction reaction, that is, before performing the heating reaction, the method S100 further includes:
[0065] S40: Add a low boiling point solvent to the mixed material and heat to 60° C.-80° C. to dissolve the mixed polyethylene glycol and the silver salt.
[0066] In some embodiments, the low boiling point solvent includes deionized water and ethanol. It is understood that the low boiling point solvent has a low boiling point and is easily evaporated and removed after reaching the boiling point.
[0067] In this embodiment, before the heating reaction, a low boiling point solvent is added to the mixture and heated to 60°C-80°C, so that the polyethylene glycol and the silver salt can be fully dissolved in the low boiling point solvent. Compared with mixing in a solid system, the liquid system can help the polyethylene glycol and the silver salt to be fully mixed, which is beneficial to improve the efficiency of the subsequent reduction reaction and the uniformity of the particle size of the nanosilver particles.
[0068] The ratio of the mass of the low boiling point solvent to the total mass of the polyethylene glycol and the silver salt is 4: 1-1: 1. Within this ratio range, the low boiling point solvent is reasonable, which can help effectively dissolve and mix the polyethylene glycol and the silver salt without causing excess low boiling point solvent.
[0069] It is understandable that, in this embodiment, 60°C-80°C does not reach the minimum temperature required for the reduction reaction, and the reduction reaction will not occur. Therefore, heating to 60°C-80°C helps the polyethylene glycol to melt and dissolve in the low boiling point solvent, and helps the polyethylene glycol and the silver salt to be fully mixed and uniform, while the reduction reaction will not occur. Therefore, the liquid system after adding the low boiling point solvent will not cause the nanosilver particles to agglomerate, and has no negative impact on the size of the nanosilver particles. On the contrary, helping the polyethylene glycol and the silver salt to be fully mixed and uniform is also beneficial to the uniformity of the particle size of the nanosilver particles.
[0070] In some embodiments, before performing the reduction reaction, the method S100 further includes:
[0071] S50: heating to a first temperature and maintaining it for a preset time to remove the low boiling point solvent, wherein the first temperature is less than 120°C and greater than 80°C.
[0072] The first temperature is greater than the boiling point of the low boiling point solvent, so that the low boiling point solvent can evaporate at the first temperature. It is understood that the first temperature is less than 120°C, that is, less than the temperature at which the reduction reaction occurs. The first temperature is greater than 80°C, that is, greater than the temperature at which polyethylene glycol melts.
[0073] It can be understood that, after the polyethylene glycol and the silver salt are fully mixed under the action of the low boiling point solvent, they are heated to the first temperature and maintained for a preset time, so that the low boiling point solvent can be evaporated, thereby removing the low boiling point solvent.
[0074] In some embodiments, the first temperature may be 105° C., and the preset time may be 30 minutes. Those skilled in the art may select a low boiling point solvent and set the corresponding first temperature and preset time according to actual conditions.
[0075] In some embodiments, during the evaporation of the low-boiling-point solvent, a vacuum device may be used, for example, vacuuming an internal mixer filled with materials to accelerate the volatilization of the low-boiling-point solvent.
[0076] In this embodiment, before the reduction reaction is carried out, the low boiling point solvent is removed, which can effectively prevent the subsequent reduction reaction process from causing the nano silver particles to agglomerate. The reaction material after the low boiling point solvent is volatilized is not only mixed evenly, but also still restored to a solid or viscous state, which can effectively limit the diffusion and agglomeration of silver ions based on the solid or viscous state, so that the particle size of the nano silver particles is relatively uniform and narrowly distributed, and its size distribution can be well controlled. Therefore, after adding a low boiling point solvent to help polyethylene glycol and silver salt mix evenly in a liquid system, the low boiling point solvent is removed again, which is conducive to improving the subsequent reaction efficiency and will not have a negative impact on the size of the nano silver particles. On the contrary, helping polyethylene glycol and silver salt to fully mix evenly is also conducive to the particle size uniformity of the nano silver particles.
[0077] In some embodiments, before performing the reduction reaction, the method S100 further includes:
[0078] S60: After the above heating to the first temperature and maintaining it for a preset time, adding an oily dispersant, wherein the ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.1%-10%.
[0079] In this embodiment, in order to prevent the oily dispersant from generating foam in the low-boiling point solvent, in the embodiment where the low-boiling point solvent is added, the oily dispersant is added after heating to the first temperature and maintaining for a preset time, that is, after removing the low-boiling point solvent. Optionally, the ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.5%-5%.
[0080] It is understandable that the oily dispersant and the role of the oily dispersant can be referred to the description in step S30, which will not be repeated here.
[0081] In some embodiments, the method S100 further includes:
[0082] S70: adding a thickener to the mixed material to increase viscosity, wherein the weight of the thickener is 1%-10% of the weight of the mixed material.
[0083] It is understandable that during the heating reaction, the polyethylene glycol and the silver salt gradually melt, and the entire material system is in a viscous state. As the reaction proceeds, the viscosity becomes smaller and smaller. In order to prevent the system viscosity from being too low so that the nanosilver agglomerates, in this embodiment, a thickener can be added to the mixture to maintain the viscosity of the system.
[0084] In this embodiment, the weight of the thickener is 1%-10% of the weight of the mixed material. By using a scanning electron microscope (SEM) to observe the morphology of the nanosilver particles prepared by adding some weight proportions of the thickener, it is found that the thickener accounting for 1%-10% of the weight of the mixed material can effectively alleviate the agglomeration of the nanosilver particles in the gradually diluted system, which is beneficial to controlling the size distribution of the nanosilver particles, so that the particle size of the nanosilver particles is more uniform and the distribution is narrow.
[0085] In some embodiments, the thickener includes high molecular weight polyvinyl alcohol, high molecular weight modified cellulose or high molecular weight starch. In some embodiments, the molecular weight of the thickener is 100,000 or more, or 1,000,000 or more. It is understood that those skilled in the art can select the thickener according to actual conditions.
[0086] In some embodiments, a thickener may be added depending on the viscosity of the material during the reaction. In some embodiments, a thickener may also be added when feeding. Specifically, when to add the thickener and the amount of the thickener to be added may be determined by those skilled in the art according to the actual viscosity, and no limitation is made here.
[0087] In some embodiments, during the reduction reaction, air or oxygen is introduced into the internal mixer or agitator.
[0088] In this embodiment, by introducing air or oxygen, polyethylene glycol can be oxidized into aldehyde and silver ions in the silver salt can be reduced into metallic silver in a high temperature and oxygen-sufficient environment. Thus, the reduction reaction can be fully carried out, and the efficiency and quality of the reduction reaction can be improved.
[0089] In some embodiments, the flow rate of the aforementioned air or oxygen is 0.01-10 L / min. It is understood that those skilled in the art can choose to introduce air or oxygen, as well as the flow rate, according to the production scale. When the production scale is large, choosing to introduce oxygen or increase the flow rate can accelerate the reduction reaction speed.
[0090] In some embodiments, the aforementioned step of “separating nanosilver particles” includes:
[0091] S21: dissolving the reaction product in water, filtering, washing and drying to obtain nano silver particles.
[0092] It is understood that the material after the reaction is completed is in a viscous state, and water is first used to dissolve the nanosilver particles in water. In some embodiments, the nanosilver particles coated with the oily dispersant may precipitate. Thus, after filtering, the nanosilver particles coated with the oily dispersant may be filtered out.
[0093] Then, the oily dispersant on the surface of the nano silver particles is cleaned with ethanol. Finally, the nano silver particles are obtained after spray drying.
[0094] In order to further illustrate the technical solution of the present application, several examples and comparative examples of prepared nanosilver particles are provided below for verification.
[0095] Embodiment 1:
[0096] Preparation of a mixed material: 8000 g of polyethylene glycol (MW 2000, solid), 1000 g of silver nitrate, 800 g of ultra-high molecular weight PE0 (MW 2000000) and 50 g of oleic acid were put into an internal mixer and mixed evenly to obtain a mixed material 1#.
[0097] Control the heating: control the temperature of the internal mixer to rise to 150°C and maintain it for 2.5 hours to heat the mixed material 1# to cause a reduction reaction.
[0098] Separating the nano-silver particles: dissolving the reaction product 1# in water, filtering, washing and drying to obtain the nano-silver particles.
[0099] Embodiment 2:
[0100] Preparation of a mixed material: 4000 g of polyethylene glycol (MW 2000, solid), 1000 g of silver nitrate, 400 g of ultra-high molecular weight PEO (MW 2000000) and 30 g of oleic acid were put into an internal mixer and mixed evenly to obtain a mixed material 2#.
[0101] Control the heating: control the temperature of the internal mixer to rise to 150°C and maintain it for 3.5 hours to heat the mixed material 2# to cause a reduction reaction.
[0102] Separating the nano-silver particles: dissolving the material 2# after the reaction is completed in water, filtering, washing and drying to obtain the nano-silver particles.
[0103] Comparative Example 1:
[0104] Prepare the solution: put 4000 g of ethylene glycol, 400 g of PVP and 400 g of silver nitrate into a reaction kettle, mix them evenly, and obtain a mixed solution 1#.
[0105] Control heating: control the reactor temperature to 150°C and maintain it for 1.5 hours to heat the mixed solution 1# to cause a reduction reaction.
[0106] Separating the nano-silver particles: filtering out the nano-silver particles from the solution 1# after the reaction is completed, and washing and drying the nano-silver particles.
[0107] Comparative Example 2:
[0108] Prepare solution: put 4000 g of polyethylene glycol (MW400, liquid) and 400 g of silver nitrate into a reaction kettle, mix well, and obtain mixed solution 2#.
[0109] Control heating: control the reactor temperature to 150°C and maintain it for 1.5 hours to heat the mixed solution 2# to cause a reduction reaction.
[0110] Separating the nano-silver particles: filtering out the nano-silver particles from the solution 2# after the reaction is completed, and washing and drying the nano-silver particles.
[0111] In Example 1, the mass proportion of silver nitrate is 10.2%, and in Example 2, the mass proportion of silver nitrate is 18.4%. In Comparative Example 1, the mass proportion of silver nitrate is 8.3%, and in Comparative Example 2, the mass proportion of silver nitrate is 9.0%.
[0112] The particle sizes of the nanosilver particles in Example 1-2 and Comparative Example 1-2 were measured using a scanning electron microscope (SEM). The measurement results are shown in Table 1 below:
[0113] Table 1 Measurement results
[0114]
[0115] As can be seen from Table 1, the reaction systems of Example 1 and Example 2 are solid or viscous, and the reaction systems of Comparative Example 1 and Comparative Example 2 are liquid. The mass proportion of silver nitrate in Example 1 is relatively low (10.2%), and the mass proportion of silver nitrate in Example 2 is relatively high (18.4%). The mass proportions of silver nitrate in Comparative Example 1 and Comparative Example 2 are both less than and close to 10%.
[0116] Generally speaking, the higher the mass proportion of silver nitrate in the solution chemical preparation method, the more nanosilver particles are prepared, the easier it is for them to aggregate and grow, and the more difficult it is to obtain nanosilver particles with uniform particle size and narrow distribution.
[0117] The particle size of the nanosilver particles in Example 1 is 50-100 nm, the particle size of the nanosilver particles in Example 2 is 50-100 nm, the particle size of the nanosilver particles in Comparative Example 1 is 100-180 nm, and the nanosilver particles in Comparative Example 2 are micron / nano particle agglomerates.
[0118] It can be seen that Examples 1 and 2 of the present application adopt the reaction system in the present application that is solid at room temperature and viscous at high temperature, and the particle size of the obtained nano-silver particles is relatively uniform and narrowly distributed, and can be controlled within 50-100nm. In particular, in Example 2, when the mass proportion of silver nitrate is relatively high, nano-silver particles with a relatively uniform particle size and a narrow distribution can still be obtained, and the particle size can be controlled within 50-100nm. The viscous reaction system of the present application can prepare nano-silver particles with a relatively uniform particle size and a narrow distribution under the condition of high silver nitrate concentration, and the particle size can be controlled within 50-100nm. The high-concentration preparation system can improve production efficiency and save production costs under the same conditions.
[0119] Comparative Example 1 uses the traditional PVP glycol reduction process, silver nitrate has a lower mass ratio, and the prepared nanosilver particles have a larger particle size and are more dispersed. Comparative Example 2 uses a liquid polyethylene glycol reduction process, silver nitrate has a relatively low mass ratio, however, the prepared nanosilver particles are micron / nano particle agglomerates, and nanosilver particles with a suitable particle size cannot be prepared.
[0120] See also Figure 2 , Figure 2 The following are micrographs of the nanosilver particles prepared in Examples 1 and 2 and Comparative Examples 1 and 2 under SEM. Figure 2 The scale of (a) is 1um. Figure 2 The scale bar in (b) is 500 nm. Figure 2 The scale bar in (c) is 500 nm. Figure 2 The scale bar in (d) is 3 um.
[0121] from Figure 2 It can be seen that the particle size of the nano silver particles in Examples 1 and 2 is relatively uniform, the distribution is narrow, the morphology is uniformly spherical, the particle size is small, and no agglomeration occurs. That is, in the reaction system in the application that is solid at room temperature and viscous at high temperature, the viscous system at high temperature can effectively limit the diffusion and agglomeration of silver particles, and even when the mass proportion of silver nitrate is high, its particle size distribution can be well controlled, so that the particle size of the nano silver particles is relatively uniform and the distribution is narrow, and the production efficiency can also be improved.
[0122] from Figure 2It can be seen that the nanosilver particles in Comparative Example 1 have a larger particle size and a wider particle size distribution, that is, the conventional PVP glycol reduction process is difficult to obtain nanosilver particles with a relatively uniform particle size and a narrow distribution when the mass proportion of silver nitrate is low. In addition, the PVP resin in Comparative Example 1 is easily left in the nanosilver particles. When the nanosilver particles are used to prepare the conductive ink, isophorone is usually required to dissolve and remove the PVP resin. However, isophorone has a strong odor and is not environmentally friendly.
[0123] Comparative Example 2 uses a liquid polyethylene glycol reaction system, and the prepared nano-silver particles are micron / nano-particle aggregates of different sizes and shapes. That is, the liquid polyethylene glycol reduction process cannot prepare silver particles with a suitable particle size when the mass proportion of silver nitrate is low, and the silver particles agglomerate.
[0124] In summary, the method for preparing nano silver particles provided in the embodiment of the present application is to mix polyethylene glycol and silver salt evenly to obtain a mixed material. The mixed material is solid at room temperature and viscous with a viscosity greater than or equal to 1000cps at high temperature. The mixed material is heated to 120°C-200°C and maintained for 2h-12h to perform a reduction reaction, and the nano silver particles are separated after the reaction is completed. In this embodiment, the mixed material used for the reaction is solid at room temperature and viscous at high temperature. This viscous system at high temperature can effectively limit the diffusion and agglomeration of silver particles, so that the particle size of the nano silver particles is relatively uniform and narrowly distributed, and its size distribution can be better controlled. In addition, polyethylene glycol is used as both a reducing agent and a reaction medium, the material is simple, no complex reagents are required, and costs can be effectively saved. It can also reduce the use of a large amount of organic matter and organic solvents, which is more environmentally friendly.
[0125] Some embodiments of the present application also provide a nano silver particle, which is prepared by the above-mentioned preparation method. The particle size distribution of the nano silver particle is narrow and has good consistency. For example, the particle size can be distributed in 50-100nm. In addition, since the preparation raw materials are simple, a large amount of organic matter and organic solvent will not be doped during the preparation process, so the purity is high and the impurities are few, which is conducive to the subsequent application of the nano silver particles.
[0126] Some embodiments of the present application also provide a conductive ink, including the aforementioned nanosilver particles, an adhesive, a solvent and an additive. Among them, the adhesive constitutes the main film-forming substance of the conductive ink, which can be a natural resin, a synthetic resin, etc. The additive can be a dispersant, a leveling agent, a thickener or a lubricant, etc. The solvent is used to dissolve the adhesive and additives in the conductive ink, adjust the viscosity, and improve the printability of the ink. The solvent can be one or more of ethylene glycol, glycerol, pinene alcohol, butyl carbitol, butyl carbitol ester, DBE, and tributyl phosphate.
[0127] It is understandable that the nanosilver particles in the conductive ink have the same structure and function as the nanosilver particles in the above embodiment, and will not be repeated here.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Under the concept of the present application, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present application as described above, which are not provided in detail for the sake of simplicity. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing nano silver particles, characterized in that: include: The solid polyethylene glycol and the silver salt are uniformly mixed to obtain a mixed material; the mixed material is solid at room temperature but is viscous with a viscosity greater than or equal to 1000 cps at high temperature; the mixed material is heated to 120° C.-200° C. and maintained for 2 h-12 h to perform a reduction reaction, and the nano-silver particles are separated after the reaction is completed.
2. The method according to claim 1, characterized in that The molecular weight of the polyethylene glycol is in the range of 600-20000.
3. The method according to claim 1, characterized in that The mass ratio between the polyethylene glycol and the silver salt is 10:1-1:
1.
4. The method according to claim 3, characterized in that The mass ratio between the polyethylene glycol and the silver salt is 5:1-1:
1.
5. The method according to claim 1, characterized in that Also includes: An oily dispersant is added to the mixed material, wherein the ratio of the mass of the oily dispersant to the mass of silver in the silver salt is 0.1%-10%.
6. The method according to claim 5, characterized in that The ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.5%-5%.
7. The method according to any one of claims 1 to 6, characterized in that: Before carrying out the reduction reaction, the method further comprises: Adding a low boiling point solvent to the mixed material and heating it to 60° C.-80° C. to dissolve and mix the polyethylene glycol and the silver salt; Wherein, the ratio between the mass of the low boiling point solvent and the total mass of the polyethylene glycol and the silver salt is 4:1-1:
1.
8. The method according to claim 7, characterized in that The low boiling point solvent includes deionized water and ethanol.
9. The method according to claim 7, characterized in that: Before carrying out the reduction reaction, the method further comprises: The low boiling point solvent is removed by heating to a first temperature and maintaining the temperature for a preset time, wherein the first temperature is less than 120° C. and greater than 80° C.
10. The method according to claim 9, characterized in that Before carrying out the reduction reaction, the method further comprises: After heating to the first temperature and maintaining it for a preset time, an oily dispersant is added, wherein the ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.1%-10%.
11. The method according to claim 10, characterized in that The ratio between the mass of the oily dispersant and the mass of silver in the silver salt is 0.5%-5%.
12. The method according to any one of claims 1 to 6, characterized in that: The method further comprises: Adding a thickener to the mixed material to increase viscosity; Wherein, the weight of the thickener is 1%-10% of the weight of the mixed material.
13. The method according to claim 12, characterized in that The thickener includes high molecular weight polyvinyl alcohol, high molecular weight modified cellulose or high molecular weight starch.
14. The method according to any one of claims 1 to 6, characterized in that: The reduction reaction is carried out in an internal mixer or a stirrer, and during the reduction reaction, air or oxygen is introduced into the internal mixer or the stirrer.
15. The method according to claim 14, characterized in that The flow rate of the air or oxygen is 0.01-10 L / min.
16. The method according to any one of claims 1 to 6, characterized in that: The separation of nano silver particles comprises: The material after the reaction is completed is dissolved in water, filtered, washed and dried to obtain the nano silver particles.
17. A nano silver particle, characterized in that: The nano silver particles are prepared by the method for preparing nano silver particles according to any one of claims 1 to 16.
18. A conductive ink, characterized in that: Comprising the nano silver particles as claimed in claim 17.